Effectiveness of Habbe Gule Aakh in Osteoarthritis Knee: A Randomized Clinical Trial - Begum, Mubasheera; Habibullah, V. (Journal of Neonatal Surgery, 2025)
Background: Osteoarthritis (OA) of the knee is a degenerative disorder leading to joint pain and functional limitations. Traditional Unani medicine has employed herbal remedies, such as Habbe Gule Aakh (HGA), to manage musculoskeletal conditions. However, empirical evidence supporting its efficacy is limited. Objective: This study aimed to evaluate the effectiveness of HGA in different doses for osteoarthritis management using clinical and radiological parameters. Methods: A randomized, single-blind, parallel-arm comparative study was conducted at the National Institute of Unani Medicine, Bengaluru. Sixty participants diagnosed with knee OA were categorized into four groups based on Kellgren-Lawrence grading. Group I received 500 mg/day, Group II 1000 mg/day, Group III 1500 mg/day, and Group IV 2000 mg/day of HGA. The assessment was conducted at baseline, and on the 7th, 14th, and 21st days using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Visual Analogue Scale (VAS). Statistical analysis included ANOVA and paired t-tests. Results: Significant improvement (p<0.001) was observed in all groups, with higher doses showing greater efficacy in reducing pain and improving joint function. No adverse effects were reported. Conclusions: HGA demonstrated promising results in knee OA management. Further large-scale studies with extended follow-ups are warranted.